PENERIMAAN PANELIS DAN SIFAT KIMIAWI EMULSI LABU KUNING DAN FRAKSI OLEIN SAWIT - Anton Rahmadi; Yuliadini Puspita; Sukmiyati Agustin; Miftakhur Rohmah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
This study aimed to produce functional food products with the main ingredient of pumpkin and olein fraction of red palm oil (OF-RPO). This research was conducted in two stages. The first was to analyze consumer acceptance where a Completely Randomized Design was used with one factor. The factor was the composition of pumpkin and OF-RPO levelled as follow: 100:0, 95:5, 90:10, 85:15, 80:20, and 0:100 (v/v). In the second stage, analyses of carotenoids using HPLC, FFA, pH, vitamin C, and peroxide values were carried out on selected formula (mixture of pumpkin and OF-RPO), formula with 100 mL of pumpkin, formula with 100 mL of OF-RPO, and negative control (without pumpkin and OF-RPO), before and after the storage period of two months, except for HPLC analysis. The best formula based on acceptance test was a composition of 90 mL pumpkin and 10 mL OF-RPO was further diluted 1:4 (v/v). Characteristics of the product were sweet, sour, not bitter, not grassy, and not rancid. The emulsion product contains trans-β-carotene at 141.65±0.47 mg/L, equivalent to 237 UI activity of vitamin A/mL. The content of trans-β-carotene was found at the highest (341.83 mg/L) from the pumpkin juice, while the OF-RPO had the lowest trans-β-carotene content (41.2 mg/L). Product was acidic with a pH of 3.6±0.1 and with vitamin C content of 13.2±1.2 mg/100 g of product. Acidity and vitamin C levels tended to remain stable during the storage period for two months. Peroxide value of the emulsion product was at 0.8 mEq oxygen/kg. The FFAs were in the range of 1.59 to 1.73% and they also did not change significantly after storage for two months.